Absence of neocytolysis in humans returning from a 3-week high-altitude sojourn - Klein, Marie; Kaestner, Lars; Bogdanova, Anna Y.; Minetti, Giampaolo; Rudloff, Silvia; Lundby, Carsten; Makhro, Asya; Seiler, Elena; van Cromvoirt, Ankie; Fenk, Simone; Simionato, Greta; Hertz, Laura; et al. (Acta physiologica, 2021)
Aims Total haemoglobin mass (tot-Hb) increases during high-altitude acclimatization. Normalization of tot-Hb upon descent is thought to occur via neocytolysis, the selective destruction of newly formed erythrocytes. Because convincing experimental proof of neocytolysis is lacking, we performed a prospective study on erythrocyte survival after a stay at the Jungfraujoch Research Station (JFJRS; 3450 m). Methods Newly formed erythrocytes of 12 male subjects (mean age 23.3 years) were age cohort labelled in normoxia (110 m) and during a 19-day high-altitude sojourn by ingestion of 13C2- and 15N-labelled glycine respectively. Elimination dynamics for erythrocytes produced in normoxia and at high altitude were measured by isotope ratio mass spectrometry of haem, by determining tot-Hb, reticulocyte counts, erythrocyte membrane protein 4.1a/4.1b ratio and by mathematical modelling. Results Tot-Hb increased by 4.7% ± 2.7% at high altitude and returned to pre-altitude values within 11 days after descent. Elimination of 13C- (normoxia) and 15N- (high altitude) labelled erythrocytes was not different. Erythropoietin levels and counts of CD71-positive reticulocytes decreased rapidly after descent. The band 4.1a/4.1b ratio decreased at altitude and remained low for 3-4 days after descent and normalized slowly. There was no indication of haemolysis. Conclusion We confirm a rapid normalization of tot-Hb upon descent. Based on the lack of accelerated removal of age cohorts of erythrocytes labelled at high altitude, on patterns of changes in reticulocyte counts and of the band 4.1a/4.1b ratio and on modelling, this decrease did not occur via neocytolysis, but by a reduced rate of erythropoiesis along with normal clearance of senescent erythrocytes.